2006
DOI: 10.2460/ajvr.67.11.1821
|View full text |Cite
|
Sign up to set email alerts
|

Influence of halothane, isoflurane, and sevoflurane on gastroesophageal reflux during anesthesia in dogs

Abstract: Maintenance of anesthesia with any of the 3 commonly used inhalant agents is associated with a similar risk for development of GER in dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1
7

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 21 publications
3
27
1
7
Order By: Relevance
“…Gastroesophageal reflux was detected in 13.3% of the anesthetized dogs in the present study, with this incidence being lower than that observed in other studies with percentages varying from 46 to 60% (Wilson et al 2005(Wilson et al , 2006aPanti et al 2009). All these studies have in common the administration of morphine as part of the pre-anesthetic medication; this seems reasonable when one takes into consideration the finding that morphine reduces EGS tone (Hall et al 1975).…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Gastroesophageal reflux was detected in 13.3% of the anesthetized dogs in the present study, with this incidence being lower than that observed in other studies with percentages varying from 46 to 60% (Wilson et al 2005(Wilson et al , 2006aPanti et al 2009). All these studies have in common the administration of morphine as part of the pre-anesthetic medication; this seems reasonable when one takes into consideration the finding that morphine reduces EGS tone (Hall et al 1975).…”
Section: Discussioncontrasting
confidence: 81%
“…This technique allows to identify reflux episodes not visualized as regurgitation, as well as to determine some anesthetic agents that predispose to reflux (Galatos and Raptopoulos 1995a, b;Raptopoulos and Galatos 1997;Wilson et al 2005Wilson et al , 2006aWilson et al , b, 2007Anagnostou et al 2009;Panti et al 2009). It has also allowed to determine that the incidence of GER episodes varies between 4.8% (Anagnostou et al 2009) and 60% (Wilson et al 2005), being influenced by several factors, such as age, type of surgical procedure (Galatos and Raptopoulos 1995a), duration of pre-operative fasting, and drugs used for pre-anesthetic medication (Galatos and Raptopoulos 1995b), induction (Raptopoulos and Galatos 1997) and maintenance (Hashim et al 1995;Wilson et al 2006a) of anesthesia.…”
Section: Introductionmentioning
confidence: 98%
“…Although the current study used only isoflurane, other volatile agents (e.g., sevoflurane) appear to produce similar PONV in patients [3]. Dogs were reported to regurgitate after exposure to halothane, isoflurane, or sevoflurarane [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Recent research indicates that ferrets do not vomit to isoflurane exposure using 2 to 4% inhaled concentrations and 10 min to 6 h of exposure (Horn et al, 2011). Dogs are reported to regurgitate after exposure to halothane, isoflurane, or sevoflurane (Wilson et al, 2006). Musk shrews vomit after exposure to halothane (inhibited by NK 1 and 5-HT 3 receptor antagonists) and isoflurane (Gardner and Perren, 1998; Horn et al, 2011).…”
Section: Stimulimentioning
confidence: 99%
“…Although there is a potential link between enhanced 5-HT 3 signaling and exposure to inhalational anesthetic agents (Machu and Harris, 1994; Parker et al, 1996), this has not been further explored in the context of emetic testing. Finally, dogs have been reported to regurgitate after exposure to halothane, isoflurane, or sevoflurane (Wilson et al, 2006) but were not specifically tested for emetic responses.…”
Section: Future Directionsmentioning
confidence: 99%